PENYALAPENYALAHGUNAAN NARKOTIKA DITINJAU DARI VIKTIMOLOGI BERDASARKAN UNDANG-UNDANG NO. 35 TAHUN 2009 DI KOTA SAMARINDAHGUNAAN NARKOTIKA DITINJAU DARI VIKTIMOLOGI BERDASARKAN UNDANG-UNDANG NO. 35 TAHUN 2009 DI KOTA SAMARINDA - Stefanus Erick Hernanda (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT Narcotics abuse victims acquire a major concern because the victim is a part that can not be separated from evil. Therefore, the victim has a very important role in victimology that facilitate in finding the response to crime that will affect the decline in the crime rate. This is consistent with the development of victimology in the settings according to the Narcotics Law No. 35 of 2009 on Narcotics.The problemsunder discussioninthis researchare1. How doesthe phenomenon ofcrimedue tomisuseandabuse of narcoticslawcrimesagainstthe victim. 2. Howthe protection ofvictims ofabuseNarcoticsaccording to LawNo. 35 of 2009on Narcotics.This research was conductedatthe National Narcotics AgencyEastKalimantannormative legalresearch methodswhich refers tothe normsandprinciples of the lawcontained in thelegislationas well asthe selectionof therelevantprovisions, namely Law No.35of2009 onNarcotics.The conclusion of this study is that the protection of victims of abuse by Narcotics Law No. 35 of 2009 on Narcotics there is a balance between the perpetrators and victims of abuse Narcotic where criminals got both criminal penalties and fines are heavy and Narcotics abuse victims get rehabilitation protection under Article 54 Narcotics Law No. 35 of 2009.       It is recommendedthatcriminal sanctionsandpenaltiescontained intheNarcoticsActis applicabletoeveryactorinvolvedabuse of narcotics. In order forthe PreventionandEradicationstrategiesAbuseandIllicitNarcotics(P4GN) whichwill belaunchedin 2014inSamarindaKaltimBNNPcanbe accomplishedso asto overcomea maximum. Keywords : Narcotics, Victim, Rehabilitations